Species Diversity of Fiddler Crabs (Uca spp.) in the Mangrove Ecosystem of Duta Coastal, Probolinggo Regency, East Java - Setiawan, Rendy; Anjani, Rifkah Ajeng; Fajariyah, Susantin; Cahyono, Haris; Kurniawan, Joko (Universitas Diponegoro, 2025)
Fiddler crab (Uca spp.) belongs to the Order Decapoda and Family Ocypodidae, which live by making burrows in the substrate between mangrove plants. The presence of fiddler crabs plays an important role in mangrove ecosystems, which can increase sediment mineralisation due to burrows that can increase oxygen distribution into the sediment. This research was conducted in the mangrove ecosystem of Duta coastal, Probolinggo Regency. The method used when sampling biota in this study is the transect-plot method, which is used to place 1x1 m2 plots systematically along the transect. Sampling of fiddler crabs was carried out at the lowest low tide. Samples taken were fiddler crabs in the plot. Data on the species found, the number of individuals of each species, and the total number of individuals obtained from species composition were used to calculate species diversity. Fiddler crabs (Uca spp.) found in the mangrove ecosystem Duta coastal were 10 species, namely U. perplexa, U. rosea, U. vocans, U. annulipes, U. triangularis, U. coarctata, U. tetragonon, U. vomeris, U. forcipata, and U. dussumieri. The diversity value of fiddler crab species in the Ambassador Coastal Mangrove ecosystem is moderate (Hˈ = 2.209). All species of fiddler crabs were found in the muddy sand substrate type, because the burrow structure is strong, so that when the tide, the burrow condition is maintained.